Analysis Factor Dominance and Contribution Program Performance against Stunting Incidents in Bali Province: SSGI Data Analysis - Suiraoka, I Putu; Nursanyoto, Hertog; Suarjana, I Made; Suastiti, Ni Made Ayu (Poltekkes Kemenkes Palu, 2024)
Since 2017, Bali Province has consistently ranked first in the lowest stunting prevalence in Indonesia. Planned programmes should be exploring and identifying certain factors which trigger stuntling, so as to reduce the prevalence of stuntin' at least in line with established distribution patterns. The data used in this research is secondary data from the Indonesian Nutrition Status Study in the Province. The analysis carried out included: Univariate analysis and multivariate analysis using backward logistic regression analysis. The results of the analysis of determinant factors and performance evaluation of the Nutrition and Health Program in Bali Province show that the factors that contribute to the stunting problem in Bali are: (a) area of residence (AOR= 1.57; 95%CI= 1.31 - 1.89); (b) PMT for pregnant women (AOR= 0.55; 95% CI= 0.39 - 0.78); (c) Pregnancy Examination (AOR= 0.83; 95%CI= 0.61 - 1.14); (d) Birth Status (AOR= 1.52; 95%CI= 1.22 - 1.90); (e) Body length at birth (AOR= 1.54 - 2.11); (f) Birth weight (AOR= 2.48; 95%CI= 1.71 - 3.58); (g) Variety of Toddler Consumption (AOR= 1.65; 95%CI= 1.36 - 2.00); and (h) Program Immunization (AOR=.0.69; 95%CI= 0.51 - 0.96). The potential for stunting occurs before the baby is born; therefore, it is recommended that priority programs be developed for women of childbearing age and pregnant women